Growing substrates for aromatic plant species in green roofs and water runoff quality: pilot experiments in a Mediterranean climate - Monteiro, Cristina M. (2017)
Green roof technology has evolved in recent years as a potential solution to promote vegetation in urban areas. Green roof studies for Mediterranean climates, where extended drought periods in summer contrast with cold and rainy periods in winter, are still scarce. The present research study assesses the use of substrates with different compositions for the growth of six aromatic plant species - Lavandula dentata, Pelargonium odoratissimum, Helichrysum italicum, Satureja montana, Thymus caespititius and T. pseudolanuginosus, during a 2-year period, and the monitoring of water runoff quality. Growing substrates encompassed expanded clay and granulated cork, in combination with organic matter and crushed eggshell. These combinations were adequate for the establishment of all aromatic plants, allowing their propagation in the extensive system located on the 5th storey. The substrate composed of 70% expanded clay and 30% organic matter was the most suitable, and crushed eggshell incorporation improved the initial plant establishment. Water runoff quality parameters - turbidity, pH, conductivity, NH4(+), NO3(-), PO4(3-) and chemical oxygen demand - showed that it could be reused for non-potable uses in buildings. The present study shows that selected aromatic plant species could be successfully used in green roofs in a Mediterranean climate.